2020
DOI: 10.1021/acscatal.0c01085
|View full text |Cite
|
Sign up to set email alerts
|

Insights in the Oxygen Reduction Reaction: From Metallic Electrocatalysts to Diporphyrins

Abstract: In the past decade, the mass activity of catalysts for the oxygen reduction reaction (ORR) has been improved mainly via increasing the number of active sites. However, little progress has been made on the improvement of the intrinsic activity of ORR catalysts; consequently, the widespread use of fuel cells is still limited by low energy efficiency. In this Perspective, we provide an overview of the fundamentals underlying the ORR on platinum-based catalysts as well as metal–nitrogen–carbon nonprecious metal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 106 publications
3
72
0
Order By: Relevance
“…11,13 A promising strategy towards this goal is the confinement of *OOH within a 3-D active site environment, which has been demonstrated for a few model systems and homogenous molecular catalysts. For instance, Rossmeisl et al 14,15 have shown that diporphyrin motifs are capable of facilitating *OOH dissociation via two closely-spaced binding sites. This approach bypasses the limitations imposed by *OOH scaling in favor of the less restrictive dissociated *O + *OH pathway.…”
mentioning
confidence: 99%
“…11,13 A promising strategy towards this goal is the confinement of *OOH within a 3-D active site environment, which has been demonstrated for a few model systems and homogenous molecular catalysts. For instance, Rossmeisl et al 14,15 have shown that diporphyrin motifs are capable of facilitating *OOH dissociation via two closely-spaced binding sites. This approach bypasses the limitations imposed by *OOH scaling in favor of the less restrictive dissociated *O + *OH pathway.…”
mentioning
confidence: 99%
“…Adapted with permission. [ 48 ] Copyright 2020, American Chemical Society. c) Theoretical plot of free energy of adsorption of HO* (ΔnormalGHO*, in light blue) and HOO* intermediates (ΔnormalGHOO*, in blue), as a function of ΔnormalGO* for metal (100) surfaces.…”
Section: Fundamentals Of Orr Electrocatalysismentioning
confidence: 99%
“…[ 1,2 ] However, the sluggish kinetics of the cathodic oxygen reduction reaction (ORR) is a key factor, determining the energy conversion efficiency of these devices. [ 3,4 ] Although platinum (Pt) and its alloy nanoparticles have proved to be the most effective and viable catalysts for ORR, its high price, low stability, and scarcity extremely hamper the commercial application. [ 5,6 ] Therefore, the exploration of non‐noble metal catalysts with excellent electrocatalytic activity, high durability, and wide‐available resources for ORR is highly desirable.…”
Section: Introductionmentioning
confidence: 99%